PENGARUH FAKTOR-FAKTOR FUNDAMENTAL TERHADAP HARGA SAHAM - Dwiarif Dianto; Tetty Lasniroha Sarumpaet (Jurnal Akuntansi Bisnis dan Ekonomi, 2019)
This research was conducted to test empirically the analysis of fundamental factors on stock prices measured using the ratio of Return On Equity (ROE) and Earning Per Share (EPS). This research was conducted on companies manufacturing consumer goods industry sectors listed on the Indonesia Stock Exchange in the period 2013-2016. The population of this study was 42 manufacturing companies in the consumer goods industry sector which were listed on the Indonesia Stock Exchange in the 2013-2016 period. The sampling technique in this study used a purposive sampling method. The sample in this study were 32 manufacturing companies in the consumer goods industry sector which are listed on the Indonesia Stock Exchange. The type of data used is secondary data from the official website of the Indonesia Stock Exchange. The results of this study prove that partially the fundamental factors using the ratio of ROE and EPS affect stock prices. Simultaneously ROE, EPS, has an influence on stock prices. The suggestion for the next researcher is to add variables that have an influence on stock prices.